Certolizumab Pegol Efficacy in Patients With Non‐Radiographic Axial Spondyloarthritis Stratified by Baseline MRI and C‐Reactive Protein Status: An Analysis From the C‐axSpAnd Study. Issue 9 (22nd June 2022) - Robinson, Philip C.; Maksymowych, Walter P.; Gensler, Lianne S.; Hall, Stephen; Rudwaleit, Martin; Hoepken, Bengt; Bauer, Lars; Kumke, Thomas; Kim, Mindy; de Peyrecave, Natasha; Deodhar, Atul
Abstract : Objective: Tumor necrosis factor inhibitors (TNFi) are an effective treatment for non‐radiographic axial spondyloarthritis (nr‐axSpA). To be eligible, however, many authorities require patients with nr‐axSpA to show active sacroiliitis on magnetic resonance imaging (MRI) and/or an elevated C‐reactive protein (CRP) level, possibly resulting in a perception that patients with nr‐axSpA without both factors have only low responses to TNFi treatment. We evaluated clinical responses to certolizumab pegol (CZP) in patients with nr‐axSpA stratified by baseline MRI/CRP status. Methods: C‐axSpAnd was a phase 3, multicenter study on CZP in adult patients with active nr‐axSpA and objective signs of inflammation. This analysis assessed efficacy of CZP over the 52‐week randomized, double‐blind, placebo‐controlled period in patients stratified into subgroups based on the presence of active sacroiliitis on MRI and CRP level at baseline. Results: CZP‐treated patients across all MRI/CRP subgroups achieved clinical responses greater than placebo. Across outcome measures, CZP‐treated MRI+/CRP+ patients demonstrated the greatest clinical responses, but substantial improvements were also observed in CZP‐treated MRI+/CRP− and MRI−/CRP+ patients. Ankylosing Spondylitis Disease Activity Score Major Improvement response rates at week 52 among CZP‐treated patients (75.6% MRI+/CRP+; 47.5% MRI−/CRP+; and 29.7% MRI+/CRP−) were higher than rates in placebo groups (range: 3.9%‐12.5%). Assessment of SpondyloArthritis international Society 40% response, Bath Ankylosing Spondylitis Disease Activity Index, and Bath Ankylosing Spondyloarthritis Functional Index had similar response patterns, although differences between the CZP‐treated MRI/CRP subgroups were smaller. Clinical responses among CZP‐treated patients were also observed in additional subgroups, including those with low Spondyloarthritis Research Consortium of Canada MRI sacroiliac joint inflammation scores and those with normal baseline CRP levels. Conclusion: Our findings indicate that CZP treatment benefits patients with nr‐axSpA across MRI+/CRP+, MRI−/CRP+, and MRI+/CRP− subgroups.